Optimal compellence - Sandeep Baliga; Tomas Sjöström (Rutgers University, Department of Economics, 2023)
In many scenarios, a protagonist tries to compel a political leader (the antagonist) to cooperate. The protagonist can impose targeted measures (e.g., "smart" sanctions) that hurt the antagonist directly, and comprehensive measures (e.g., trade embargoes) aimed at provoking a popular uprising against the antagonist. However, there is no uprising if the citizens think the antagonist is defending their interests against a hostile protagonist: the rally-'round-the-flag effect. The effectiveness of the protagonist's compellent policy depends on the complex ways in which it influences the rally-'round-the-flag effect. First, there is the direct impact on costs and benefits. Second, the policy may signal the protagonist's level of hostility. Third, the policy influences the antagonist's "political bias", i.e., the misalignment between his interests and those of the representative citizen. We study the optimal mix of targeted and comprehensive measures, and whether the different measures are substitutes or complements.
Keywords: F51; 330; Conflict; Sanctions